Effect of edaphic and foliar applications of different doses of zinc on the yield of the criolla colombia cultivar (2014)
The present study was carried out in a Typic Hapludand soil in the municipality of ‘El Rosal’ (Colombia) and aimed to compare the yield performance of the cultivar Criolla Colombia under foliar applications of Zn chelate (0, 1, 2 and 3 kg ha-1) and edaphic applications of granulated Zn sulfated (0, 1, 2 and 3 kg ha-1). A split-plot, randomized complete block design, with four repetitions per treatment, was employed. In each category, the evaluated variables were: tuber weight and number of tubers. The results revealed that the 3.0 kg ha-1 edaphic application rendered a quadratic yield behavior with a relative increase of 7.9 t ha-1 (136%) for the first category tuber weight and 9.5 t ha-1 (68%) for total weight. In turn, the foliar application of the same dose resulted in a 5.8 t ha-1 (93%) relative increase and a first category tuber total weight increase of 3.8 t ha-1 (24%). Under the edaphic and foliar Zn applications, the number of tubers underwent 77 and 86% increases, respectively, with respect to the control. These results show the importance of Zn in photoassimilate accumulation efficiency, structure differentiation and tuber quality in this short-cycle crop.